Perkawinan Manusia dengan Jin: Kajian atas Naskah Ākām al-Marjān fī Ahkām al-Jān - Ahmad Yunani (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2018)
In some stories circulating in the community, as well as in some writings, there is information about the existence of marriages of humans with supernatural beings (jinns). For example, the marriage story between Panembahan Senopati and Ratu Kidul, an event that seems impossible to occur because of two different realms, namely the real world with the supernatural. However, this event can occur, whether human beings with supernatural beings, or vice versa, with specific goals and objectives, such as seeking wealth, immunity, magic, and various other pleasures according to the wishes of the culprit. In the text of Ākām al-Marjān fī Ahkām al-Jān, there is one chapter that explains this, namely the existence of a relationship between humans and jinn, and vice versa, in various aspects. One of them is in the form of a marriage bond. It was also explained about the legal consequences it caused, especially about whether or not the action was carried out. This text is written in Arabic. This paper tries to reveal the matter of human marriage with jinn based on the text. The approach used is the philology and textual analysis. The philology is used to produce text editions. Then equipped with the translation in Indonesian. While the textual analysis is carried out on the contents of the text, namely an explanation of the occurrence of marriage between humans and jinn, indicators of the relationship between the two, and the arguments related to the prohibition of marriage.Keywords: Marriage, jinn, Imam Malik, law, Ahkām al-Jān, textDalam beberapa cerita yang beredar di masyarakat, demikian pula dalam beberapa tulisan, terdapat informasi tentang adanya peristiwa perkawinan manusia dengan makhluk gaib (bangsa jin). Misalnya, cerita perkawinan antara Panembahan Senopati dan Ratu Kidul, sebuah peristiwa yang tampaknya mustahil terjadi karena dua alam yang berbeda, yakni alam nyata dengan alam gaib. Akan tetapi, peristiwa ini bisa terjadi, baik manusia dengan makhluk gaib tersebut, maupun sebaliknya, dengan tujuan dan maksud tertentu, seperti mencari kekayaan, kekebalan tubuh, kesaktian, dan berbagai kesenangan lainnya sesuai keinginan pelakunya. Dalam naskah Ākām al-Marjān fī Ahkām al-Jān, terdapat satu bab yang mejelaskan hal tersebut, yaitu adanya hubungan antara manusia dengan jin, dan sebaliknya, dalam berbagai aspek. Salah satunya adalah adalah dalam bentuk ikatan perkawinan. Dijelaskan pula tentang akibat hukum yang ditimbulkannya, khususnya tentang boleh atau tidaknya perbuatan itu dilakukan. Naskah ini ditulis dengan aksara dan bahasa Arab. Tulisan ini mencoba mengungkap perihal perkawinan manusia dengan jin berdasarkan naskah tersebut. Pendekatan yang digunakan adalah pendekatan filologi dan analisis tekstual. Pendekatan filologi digunakan untuk menghasilkan edisi teks. Kemudian dilengkapi dengan terjemahannya dalam bahasa Indonesia. Sedangkan analisis tekstual dilakukan atas isi dari naskah tersebut, yaitu penjelasan tentang terjadinya perkawinan antara manusia dengan jin, indikator adanya huhubungan antar keduanya, dan dalil-dalil yang terkait dengan larangan perkawinan tersebut.Kata kunci: Perkawinan, jin, Imam Malik, hukum, Ahkām al-Jān, teks.